Commoning Practices in Data-Driven Society & Architecture Education (EAAE Annual Conference Proceedings, 2023)
The paper examines the role of commoning practices in data-driven society, placing particular emphasis on their role in the establishment of new agendas in architectural education. As Patrick Bresnihan underscores, in “The More-than-human Commons: From Commons to Commoning”, “[t]he noun ‘commons’ has been expanded into the continuous verb ‘commoning’ to denote the continuous making and remaking of the commons through shared practice.” Stavros Stavrides’s claim that “[c]ommoning practices importantly produce new relations between people” is at the core this paper given that its main objective is to examine the impact of commoning practices on the relations between citizens in data-driven society.